2014
DOI: 10.1007/s11033-014-3808-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of placental and maternal stress responses in patients with pregnancy related complications via monitoring of heat shock protein mRNA levels

Abstract: The study describes the stress response in the central cotyledon zone of placental tissue and in maternal whole peripheral blood to pregnancy related complications including gestational hypertension (n = 31), preeclampsia w or w/o fetal growth restriction (n = 95), and fetal growth restriction (n = 39) using real-time RT-PCR and genes encoding Hsp27, Hsp60, Hsp70, Hsp90 and HspBP1 proteins. The placental tissue does not respond to pregnancy induced hypertension, fetal growth restriction and short-term severe p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 37 publications
1
25
0
2
Order By: Relevance
“…As we previously explained, this can also be accomplished through PI3K and the involvement of AKT1. The expression of HSP90 could be polemic because apparently it is related with the disease progression and also placenta location [68]. However several authors had being found an increment in the placenta expression of HSP90 in PE [6870] at mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…As we previously explained, this can also be accomplished through PI3K and the involvement of AKT1. The expression of HSP90 could be polemic because apparently it is related with the disease progression and also placenta location [68]. However several authors had being found an increment in the placenta expression of HSP90 in PE [6870] at mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…In severe early-onset FGR, there is increased expression of genes regulating intrinsic apoptosis in both the placenta and maternal blood (Whitehead et al, 2013). AHSA2 AHA1, activator of heat shock 90 kDa protein ATPase homolog 2 The upregulation of Hsp90, found in placental tissues affected with mild preeclampsia (Hromadnikova et al, 2015), may be associated with downregulation of miR-520a* and miR-525. Both microRNAs have been predicted to regulate the expression of the AHSA2 gene, which is an activator of Hsp90 protein ATPase homolog 2.…”
Section: Gene Official Symbolmentioning
confidence: 99%
“…Heat shock transcription factory family member 5 The upregulation of Hsp27, Hsp90, and HspBP1, found in placental tissues affected with mild preeclampsia (Hromadnikova et al, 2015), may be associated with downregulation of miR-520a* and miR-525. Both microRNAs have been predicted to regulate the expression of HSF5 gene, a transcriptional activator of heat shock genes.…”
Section: Hsf5mentioning
confidence: 99%
See 1 more Smart Citation
“…Hsp70 concentrations are also elevated in placental tissues from women with preeclampsia, especially in those with early onset disease (Yung et al 2014). More recently, hsp70 mRNA levels in whole blood were found to be significantly elevated in gestational hypertension, preeclampsia, and IUGR (Hromadnikova et al 2015). Variations in the expression of autophagic markers (Gao et al 2015) and hsp70 levels (Johnstone et al 2011) in preeclamptic placentae at different gestational ages may be an example of the pathological dysregulation of these two processes that contribute to the development of preeclampsia.…”
Section: Placental Developmentmentioning
confidence: 99%